Markers for human haematopoietic stem cells: The disconnect between an identification marker and its function - Rix, Beatrice; Maduro, Andres Hernandez; Bridge, Katherine S.; Grey, William (Frontiers in Physiology, 2022)
The haematopoietic system is a classical stem cell hierarchy that maintains all the blood cells in the body. Haematopoietic stem cells (HSCs) are rare, highly potent cells that reside at the apex of this hierarchy and are historically some of the most well studied stem cells in humans and laboratory models, with haematopoiesis being the original system to define functional cell types by cell surface markers. Whilst it is possible to isolate HSCs to near purity, know very little about the functional activity of markers to purify HSCs. This review will focus on the historical efforts to purify HSCs in humans based on cell surface markers, their putative functions and recent advances in finding functional markers on HSCs.